2010
DOI: 10.3109/09286586.2010.508351
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Surgical Strabismus in Saudi Arabia

Abstract: The ratio of esotropia to exotropia in our study is comparable to previous studies done in predominantly European and Middle Eastern populations. Surgical esotropia decreased with age while surgical exotropia increased. Overall, our rates of sensory strabismus were much higher than previously reported, even if we compare only the younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
4
11
0
Order By: Relevance
“…(2010) data regarding strabismus in Saudi Arabia [34]. The high incidence of strabismus in our study is in line with the other studies related to vision screening among school children in Saudi Arabia [35,36].…”
Section: Discussionsupporting
confidence: 90%
“…(2010) data regarding strabismus in Saudi Arabia [34]. The high incidence of strabismus in our study is in line with the other studies related to vision screening among school children in Saudi Arabia [35,36].…”
Section: Discussionsupporting
confidence: 90%
“…Although concomitant convergent squint is more prevalent with hypermetropia (9)(10) (11) , hypermetropia could be used also as a predictor more than emmetropia (12) .In our study we found that hypermetropia and esotropia were most prevalent among concomitant squint patients this is going with results from pakistan (3)Saudi Arabia (13) ,Italy (14),Ethiopia and Nigeria (3)(17)(18), on the other hand myopia was the least prevalent with 6.9%(8.075 :1) of the cases ;this is totally contrasting the Chia A et al (15) study where myopia: hypermetropia represents 7:1and Yekta A(16) and also extotropia in contrast to our data where convergent squint predominates , this could be answered by the difference in ethanic races (13) between Caucasian and Asian race .…”
Section: Discussion:-supporting
confidence: 75%
“…6,33,38,39 Nevertheless, exotropia has been reported to be more prevalent in Asians than Caucasians although the prevalence of esotropia has been shown to be higher in Saudi Arabia. 7,17,[27][28][29][30][31] It is interesting that reports from Japan are contradictory as esotropia is more prevalent in some studies and exotropia in others. 40,41 However, it seems that the type of refractive error is one of the most important reasons for the variety in the type of strabismus.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The prevalence of strabismus ranges from less than 0.5% to about 5% in different communities and countries. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, the prevalence is substantially higher in some diseases, such as Down or Marfan syndrome. 21,26 Available population-based studies on strabismus have mostly addressed binocular vision problems besides amblyopia and very few studies have exclusively evaluated strabismus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation